2020
DOI: 10.4269/ajtmh.20-0029
|View full text |Cite
|
Sign up to set email alerts
|

An In-Depth Examination of Reasons for Autopsy Acceptance and Refusal in Northern Tanzania

Abstract: Uncertainty about the causes of death (COD) in low-and middle-income countries (LMICs) has been recognized as a constraint to global health and development. Although complete diagnostic autopsy (CDA) is the best way to assess COD, it is uncommon in LMICs because of low investment priority and assumptions about poor acceptability. Social science research was conducted from May 2016 through July 2017 to examine issues related to acceptability of CDAs in northern Tanzania where autopsy was being offered in two re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
(44 reference statements)
1
4
0
Order By: Relevance
“…Adverse media attention especially, in retaining organs, is another reason for the refusal of autopsy [28]. Studies across the world also find similar reasons for refusing autopsy, which was observed in our study [29][30][31][32]. Age, sex, and occupation did not alter participants' opinions on postmortem examination; however, participants from the Hindu religion felt that performing customary burial rites for the deceased was more challenging in conventional postmortem.…”
Section: Discussionsupporting
confidence: 78%
“…Adverse media attention especially, in retaining organs, is another reason for the refusal of autopsy [28]. Studies across the world also find similar reasons for refusing autopsy, which was observed in our study [29][30][31][32]. Age, sex, and occupation did not alter participants' opinions on postmortem examination; however, participants from the Hindu religion felt that performing customary burial rites for the deceased was more challenging in conventional postmortem.…”
Section: Discussionsupporting
confidence: 78%
“…Research conducted in Tanzania with multiple participant groups demonstrated that autopsy was accepted and religious factors were facilitators to the acceptance, not barriers. Conducting CDA in this context was often done to learn the cause of death thus being able to determine if witchcraft was involved, which were sourced from local religious beliefs, especially in case of sudden death of a person who had no illness history [22].…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…The gold standard for obtaining accurate causes of death information is a complete diagnostic autopsy, more often, the procedure is not even suggested as it is not typically feasible in LMICs because of the expense, required expertise and, in some settings many families decline the procedure for personal, socio-cultural, and religious reasons [8][9][10][11]. During the past decade, use of post-mortem specimens collected through minimally invasive tissue sampling (MITS) has shed light on the sequence of events leading to deaths in children [12,13].…”
Section: Introductionmentioning
confidence: 99%